2020
DOI: 10.1371/journal.pone.0240803
|View full text |Cite
|
Sign up to set email alerts
|

Association between diet-related greenhouse gas emissions and nutrient intake adequacy among Japanese adults

Abstract: Objectives A growing number of Western studies have been exploring sustainable and healthy dietary patterns that target to reduce diet-related greenhouse gas emissions (GHGE) and to achieve nutritional needs. However, research is limited among Asian populations, where food sources for diet-related GHGE differ from those in Western populations. This study aimed to investigate associations between diet-related GHGE and the prevalence of inadequate nutritional intake. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…Nevertheless, the second food group in terms of contribution to diet-related GHGE was fruits and vegetables, and high-GHGE diets contained greater percentage contributions from this food group to total GHGE than did low-GHGE diets. This last result regarding vegetable intake is consistent with findings of Sugimoto et al (105) and confirms that intake of certain plant-based foods can also be associated with high GHGE, depending on the amount and type of products selected (106) .…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the second food group in terms of contribution to diet-related GHGE was fruits and vegetables, and high-GHGE diets contained greater percentage contributions from this food group to total GHGE than did low-GHGE diets. This last result regarding vegetable intake is consistent with findings of Sugimoto et al (105) and confirms that intake of certain plant-based foods can also be associated with high GHGE, depending on the amount and type of products selected (106) .…”
Section: Discussionsupporting
confidence: 91%
“…Macronutrient inadequacy has been documented in Japan [26][27][28] and in many other countries [7,15,18,19,21,24]. Our results similarly indicated that the percentage of energy intake from energy-providing nutrients (i.e., protein, carbohydrates, and total and saturated fats) was inadequate for most age groups in both sexes.…”
Section: Macronutrient Inadequacysupporting
confidence: 81%
“…Insufficient dietary fibre intake has been reported worldwide [1,12,15,19,26,27,49]. Our investigation found that adolescents and adults did not consume enough dietary fibre.…”
Section: Macronutrient Inadequacymentioning
confidence: 45%
“…Food production is a cause of GHG emissions, and the shift in dietary patterns affects both environment and health (Aleksandrowicz et al, 2016). The food industry creates 20-30% of total GHG emissions and livestock meat production plays a large role in the industry (Sugimoto et al, 2021). Given that meat production is driven by consumer demand, there is a need to change dietary patterns (Lucas and Horton, 2019).…”
Section: Introductionmentioning
confidence: 99%